PERFORMANCE VARIABILITY OF STATE OWNED ENTERPRISES IN FINANCIAL SECTOR AND FINANCIAL TECHNOLOGY COMPANIES DURING THE COVID-19 PANDEMIC - Axel Giovanni; Devi Wahyu Utami; Alifa Jauzaa; Clarisa Alfa Lionora (Universitas Airlangga, 2021)
This study aims to provide empirical evidence related with financialsector performance and the development of fintech lending inIndonesia during the Covid-19 pandemic. The sample consisted of4 State-Owned Enterprises (BUMN) in the financial sector and 149financial technology (fintech) companies registered in the FinancialServices Authority (OJK). This research used descriptive statistics.The results show that during the Covid-19 pandemic, theperformance of State-Owned Enterprises (SOEs) in the financialsector and financial technology companies (fintech) has increased.However, the increase in the performance of State-OwnedEnterprises (SOEs) in the financial sector and financial technology(fintech) companies during pandemic was still below theperformance increase before the Covid-19 pandemic in Indonesia.